Recurrence of Renal Hydatid Cyst - Basnet, Robin Bahadur; Regmi, Prabodh; Adhikari, Baikuntha; Gharti, Binod Babu; Basnet, Surendra; Mishra, Udita (Nepalese Medical Journal, 2022)
Hydatid cyst is a zoonotic disease caused by Echinococcus granulosus, transferred through the oral-fecal pathway by eating vegetables and food contaminated with dog stool containing eggs of the parasite. Hydatid cyst is most commonly found in the liver; however, dissemination can occur in other organs such as the lung and rarely in the heart, breast, thyroid, soft tissue of the neck, and kidney. The surgical approach remains the treatment of choice in hydatid. Meticulous handling of hydatid is important preoperatively and care should be taken against spillage of the contents and daughter cysts. In this case report, we report a case of recurrence of renal hydatidosis.